Current Status of Cell-Based Therapies for COVID-19: Evidence From Mesenchymal Stromal Cells in Sepsis and ARDS - Xu, Zhiheng; Huang, Yongbo; Zhou, Jianmeng; Deng, Xiumei; He, Weiqun; Liu, Xiaoqing; Li, Yimin; Zhong, Nanshan; Sang, Ling (Frontiers in Immunology, 2021)
The severe respiratory consequences of the coronavirus disease 2019 (COVID-19) pandemic have prompted urgent need for novel therapies. Cell-based therapies, primarily using mesenchymal stromal cells (MSCs), have been demonstrated safety and possible efficacy in critical illness, particularly in sepsis and acute respiratory distress syndrome (ARDS). However, limited pre-clinical data with MSCs was found in COVID-19. Recent studies have shown that MSCs could decrease inflammation, improve lung permeability, enhance microbe and alveolar fluid clearance, promote lung epithelial and endothelial repair. In addition, MSC-based therapy has shown promising effects in preclinical studies and phase 1 clinical trials in sepsis and ARDS. Here, we review recent advances related to the MSC-based therapy in context of sepsis and ARDS and evaluate the potential value of MSCs as therapeutic strategy for COVID-19.